Oral cancer awareness among dental patients attending polyclinic, kulliyyah of dentistry, International Islamic University Malaysia (IIUM): a preliminary study - Abllah, Zurainie; Tin, Myo Han; Hassan, Haszelini; Jamani, Nurjasmine Aida; Abd. Aziz, Karimah Hanim (2015)
Introduction: Oral cancer is the 6th most common cancers worldwide. Malaysia ranks at no-14 in the world with the age adjusted death rate 7.72 per 100,000 populations. Although, survival of early detected oral cancer is high, many people present in late stages because of their low awareness. This study aims to assess the awareness of dental patients on oral cancer and its relation to socio-demographic background.